From Centralization to Empowerment: Exploring Decentralized Governance in Pakistan for Sustainable Development - Dr. Farzana Zaheer Syed; Dr Usman Qais; Dr. Tahira Mumtaz (Journal of Peace, Development and Communication, 2023)
The research paper aims to investigate the shift from a centralized governance model to a decentralized one in Pakistan, concentrating on its impact on empowerment and its contribution to sustainable development. In recent years, many countries, including Pakistan, have recognized the limitations of centralized governance systems in effectively addressing local needs and promoting sustainable development. Decentralized governance, with its emphasis on devolving decision-making authority to local levels, has gained prominence as a means to empower communities and enhance development outcomes. This research adopts a qualitative methods approach to comprehensively examine the dynamics of decentralized governance in Pakistan. Moreover, the research explores into the extent to which decentralized governance has contributed to sustainable development outcomes for instance improved service delivery, enhanced citizen participation, local economic growth, and environmental conservation. It also identifies challenges and constraints that have emerged during this transition, analyzing the policy and institutional frameworks that have facilitated or hindered its effective implementation. By exploring participatory practices, institutional mechanisms, and stakeholder perspectives, this study aims to offer insights into the practical implications of the shift from centralization to empowerment through decentralized governance. The findings are anticipated to subsidize to a better understanding of the complex relationship between governance structure, local empowerment, and sustainable development, while providing recommendations for policy and practice to improve the benefits of decentralized governance in Pakistan’s voyage toward sustainable development.